Dexmedetomidine and magnesium sulphate as the anaesthetic adjuncts for intraoperative management for resection of pheochromocytoma - a case report - Shrestha, Gentle Sunder; Rupakhetee, Sachit Sharma; Pathak, Sunil; Acharya, Pragya; Parajuli, Bashu Dev; Shrestha, Anil (Journal of Society of Anesthesiologists of Nepal, 2016)
Pheochromocytoma, a tumour arising from adrenal medulla or other ganglia of sympathetic nervous system is notorious for secreting catecholamines. This form of the tumour is a major challenge to anaesthesia team as acute changes in blood pressure and heart rate usually occurs due to the release of catecholamines from the tumour site before tumour resection and cessation of the same after resection leading to hemodynamic instability intraoperatively. Better hemodynamic stability is desired during this form of tumour resection as acute fluctuations in blood pressure may lead to severe intracranial or cardiovascular events. Dexmedetomidine and magnesium sulphate were used as anaesthetic adjuncts to achieve good hemodynamic stability in a 35 years old female who presented with the history of headaches, palpitation and sweating on and off since last 2 years. The use of these agents allowed us to obtain an acceptable level of hemodynamic stability along with the help of other agents such as inotropes, vasopressors, vasodilators and antihypertensive agents. Dexmedetomidine and magnesium sulphate were used before resection of the tumour in our case and stopped thereafter. These agents may be an excellent option as anaesthetic adjuncts to obtain greater hemodynamic stability during resection of pheochromocytoma.